Initial chest X-ray in multiple trauma patients: Still works! - Koci, Jaromir; Kocova, Eva; Hyspler, Radomir; Lochman, Petr; Berkova, Jana; Trlica, Jan; Dedek, Tomas (Neuro endocrinology letters, 2019)
OBJECTIVE: Blunt thoracic aortic injury is life-threatening injury. High suspicion on this clinical condition can be made by initial chest X-ray on emergency department. The aim of study was to detect which other signs, except widened mediastinum, are specific for rupture of the thoracic aorta. METHODS: To the study were included all Triage positive patients primary headed from the scene of injury to the Trauma center Level I from January to December 2014 and which have performed chest X-ray on emergency department followed by CT of chest, abdomen and pelvis. On chest X-ray were evaluated diameter of superior mediastinum, deviation of trachea, deviation of left and right main bronchus, aortic arch, fracture of first or second rib on the left side and obliteration of aortopulmonary space. RESULTS: Totally n=208 patients were enrolled to the study. Seven patients had blunt thoracic aortic injury on CT angiography. All these patients had widened superior mediastinum more than 80 mm (p=0.021). Six patients with blunt thoracic aortic injury had obliteration of aortic arch (p=0.0001) and obliteration of aortopulmonary space (p=0.0001). CONCLUSION: All patients after high energy trauma with widened mediastinum together with obliteration of aortic arch and obliteration of aortopulmonary space on initial chest X-ray without initial CT, must be indicated to the CT after initial stop the bleeding procedures for the exclusion of traumatic rupture of thoracic aorta.
Keywords: dospělí; ruptura aorty; polytrauma; Female; skóre závažnosti úrazu; Aorta, Thoracic; Mediastinum; Adult; ženské pohlaví; Computed Tomography Angiography; Bronchi; Injury Severity Score; Multiple Trauma; Trachea; Wounds, Nonpenetrating; lidé; mediastinum; bronchy; Rib Fractures; trachea; Radiography, Thoracic; zkrácená stupnice závažnosti úrazů; kohortové studie; tupá poranění; Cohort Studies; retrospektivní studie; Male; aorta thoracica; fraktury žeber; rentgendiagnostika hrudníku; Thoracic Injuries; Abbreviated Injury Scale; mužské pohlaví; CT angiografie; Retrospective Studies; Aortic Rupture; poranění hrudníku; Humans